Integrasi Kecerdasan Buatan dalam Manajemen Keberlanjutan: Membangun Model Bisnis yang Berkelanjutan - Panca Hadi Suryatno (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
In the evolving digital era, the integration of artificial intelligence (AI) in sustainability management is increasingly becoming a key focus for companies seeking to achieve sustainability goals. This research aims to explore how AI can be applied to improve operational efficiency, minimize environmental impact, and enhance corporate social responsibility. Approximately 70% of companies worldwide feel unprepared to address sustainability challenges. On the other hand, AI offers significant potential to optimize resource use and improve decision-making. This research identifies various ways in which AI can be used in resource management, sustainable product and service innovation, ethical challenges, and implementation strategies. Using a qualitative approach, this research analyzes data from in-depth interviews and case studies to provide more comprehensive insights into best practices in integrating AI and sustainability. The results show that companies adopting AI technology are not only able to improve their sustainability performance but also create long-term value for stakeholders. This research is expected to make a significant contribution to the existing literature and serve as a practical guide for companies integrating AI into their sustainability strategies.